Protocolo local de indicaciones quirúrgicas en lesiones por presión - González A., Tomás; Benítez S., Susana; Erazo C., Cristián; Danilla E., Stefan; Domínguez C., Carlos; Albornoz G., Claudia; Sepúlveda P., Sergio (Revista Hospital Clínico Universidad de Chile, 2023)
No abstract available